Implementing an Injury Prevention Briefing to aid delivery of key fire safety messages in UK children’s centres: qualitative study nested within a multi-centre randomised controlled trial - Beckett, Kate; Goodenough, Trudy; Deave, Toity; Jaeckle, Sally; McDaid, Lisa; Benford, Penny; Hayes, Mike; Towner, Elizabeth; Kendrick, Denise (BioMed Central, 2014)
Background